European distance learning experience at higher educational institutions in ukraine - Rozhenko, Inessa Vitalievna; Aheicheva, Oleksandra Oleksandrivna; Derkunska, Zhanna Viktorivna; Pshychkina, Natalia Georgievna (НТУ "ХПИ", 2018)
The problem of European distance learning experience implementation at higher educational institutions of Ukraine is considered. The relevance of the article due to the need of implementation of distance learning and use of the opportunities offered by on-line learning. Existing practices and methods of ensuring the quality of distance learning, which create the necessary foundation for scientific achievements are systematized and analyzed in the article. The study of conceptual ideas of distance education in the European Higher Education Area, the definition of further perspectives for the development of domestic practices in the implementation of information and communication technologies in the distance education is investigated. The comparative analysis is based on sources of information collected and analyzed using European countries standards for monitoring colleges and universities.

В работе рассмотрена проблема реализации европейского опыта дистанционного обучения в Высших учебных заведениях Украины. Актуальность этой работы обусловлена необходимостью внедрения дистанционного обучения и использованием возможностей, которые предоставляет электронное обучение. В статье систематизированы и проанализированы существующие методы и методы обеспечения качества дистанционного обучения, которые создают необходимую основу для научных достижений. Исследуется изучение концептуальных идей дистанционного обучения в Европейском пространстве высшего образования, определение дальнейших перспектив развития отечественной практики в области внедрения информационно-коммуникационных технологий в дистанционном обучении
Внедрение европейского опыта дистанционного обучения в высших учебных заведениях Украины
Keywords: distance education; on-line learning; ICT; электронное обучение; информационно-коммуникативные технологии ИКТ; обеспечение качества; научные достижения